Evaluation of mechanical strength of combined natural fiber reinforced polymer composites. Issue 1 (December 2020) - Saravanan, M; Krishnamoorthi, Sangeetha; Karthik, N; Kavin Kumar, S; Nikhil Krishnan, V
Abstract: By witnessing the evolution of material science in the engineering fields, many engineering products are manufactured by fiber reinforced composites instead of metals. Most of the industries shows interest in these polymer composites than the metals because of their advanced properties and their easiest way of manufacturing processes. In this project natural fiber reinforced polymer composites (NFRPCs) were fabricated using hand layup method. This project aims at investigating the mechanical properties of the NFRPCs in order to fabricate this material by the cheapest and easiest way. Here three composite plates were manufactured, where Bamboo bark or (Bamboo Culm) and typha angustifolia (cattail) were used as reinforcing material and General epoxy resin was used as a strong adhesive material to bind these fiber. These three plates are to be compared. One of the plates is random chemical treated; the second is bi-directional chemically treated and the third plate is unidirectional chemically treated. The mechanical properties in this study include the tensile, impact strength and flexural modulus. The flexural test was taken at these plates and with the help of test's results. Mechanical properties of the plates were compared and the plate which has more strength can be selected.